Akash Asked a Question
January 22, 2021 6:30 pmpts 30 pts
If y(x) satisfies the differential equation +2y = 2+e* with y(0) = 0, then t y(x) is equal to dx Ex. (A) (B) 1 (C) 2 (D) 1 Sol. Given differential equation is a first order linear differential equation. 2dx LF. = e = e2x. Therefore the solution is y.e =[(2e +e- dx y.e* = e+|e dxy 1+ee dxLt y(x)=1 X
  • 1 Answer(s)
  • 0 Likes
  • 1 Comments
  • Shares
  • Indrajeet maurya thankyou
    see the attachment
    • cropped4336067339216041312.jpg
    Likes(0) Reply(0)